Delay aversion - Efe A. Ok; Jean-Pierre Benoît (Theoretical Economics, 2007)
We address the following question: When can one person properly be said to be more delay averse than another? In reply, several (nested) comparison methods are developed. These methods yield a theory of delay aversion which parallels that of risk aversion. The applied strength of this theory is demonstrated in a variety of dynamic economic settings, including the classical optimal growth and tree cutting problems, repeated games, and bargaining. Both time-consistent and time-inconsistent scenarios are considered.
Keywords: D11; D90; 330; Delay aversion; impatience; consumption smoothing; time consistency